KÜRESELLEŞME SÜRECİNDE KOBİ'LERİN E-TİCARETE UYUMU - YILMAZ, AHMET ERAY (Fırat Üniveristesi, 2019)
Bilgi toplumunun geleceğimizi şekillendirdiği günümüzde, teknolojik gelişmelerin etkisiyle ekonomimiz de evirilmektedir. Bu kapsamda ekonomimiz için kilit noktada bulunan KOBİ'ler her türlü gelişmelere ayak uydurmak zorundadır. Gelişen ekonomilerin en önemli sorunu ise sürdürülebilir ekonomik büyümedir. Dünyada ve ülkemizde ekonomik büyümenin lokomotifi ise, düşünüldüğü gibi çok ünlü markalar, şirketler değil, "Küçük ve Orta Büyüklükte Şirketler" dediğimiz "KOBİ'lerdir. İnternetin hızla yaygınlaşması, elektronik ticareti, ticari işlemlerin yürütülmesinde yeni ve çok etkin bir araç haline getirmiştir. Elektronik ticaret dünyadaki ekonomik sistemin serbestleşmesi ile birlikte son on yılda yaşanan ve bilgi iletişimini kolaylaştıran teknolojik gelişmelerin bir ürünü olarak ortaya çıkmıştır. Bu teknolojik gelişmeler sayesinde yeni pazarlara açılmanın önü açılmıştır. Bu çalışmada KOBİ'lerin, e-ticaret ile birlikte artan rekabet gücü konusu ele alınacaktır.

Today, when the information society is shaping our future, our economy is also evolving due to technological developments. In this context, SMEs, which are in a key position for our economy, have to keep up with all kinds of developments. The most important problem of developing economies is sustainable economic growth. On the other hand, the locomotive of economic growth in the world and in our country is not the very famous brands and companies as we thought, but the "Small and Medium Sized Companies" which we call SMEs. The rapid expansion of the internet has made electronic commerce a new and very effective tool in the execution of commercial transactions. Electronic commerce has emerged as a product of the technological developments that have occurred in the last decade and facilitated information communication along with the liberalization of the economic system in the world. Thanks to these technological developments, the opening of new markets has been opened. In this study, the issue of increasing competitiveness of SMEs with e-commerce will be discusse
Adaptation of SMES to e-commerce in the globalization process
Keywords: İşletme